Relationships matter: How clinicians can support positive parenting in the early years. Issue 5 (25th July 2019) - Williams, Robin C; Biscaro, Anne; Clinton, Jean
Abstract: A secure attachment relationship with at least one healthy adult is essential for a child to develop optimal coping abilities. Primary care providers like paediatricians and family physicians can help by supporting parents in practice settings. Every clinician encounter is an opportunity to ask parents about children's relationships and their behaviour, daily routines, and overall family function. This statement, which focuses on children aged 0 to 6 years, describes basic principles in support of positive parenting and recommends in-office practices to promote secure parent–child relationships, engage families and build trust with parents. Crying, sleep, and difficult behaviours are described as opportunities for clinicians to provide anticipatory, responsive guidance to parents.